2014
DOI: 10.3390/w6123783
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil and Water Conservation Measures on Groundwater Levels and Recharge

Abstract: Abstract:Measures of soil and water conservation (SWC) could affect the hydrological process. The impacts of typical measures on groundwater recharge, levels and flow were analyzed based on simulated rainfall experiments and a groundwater model. The three-dimensional finite-difference groundwater flow model (MODFLOW) was calibrated and verified for bare slope, grassland and straw mulching scenarios based on the experiments. The results of the verification in groundwater balance, levels, runoff and flow field a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The experiments were conducted in the sand-box model [42,43], 5.3 m × 1 m × 1 m, at the Rainfall Simulation Hall. The slope of the model could be adjusted manually from 0° to 35°.…”
Section: Experimental Conditions and Equipmentmentioning
confidence: 99%
“…The experiments were conducted in the sand-box model [42,43], 5.3 m × 1 m × 1 m, at the Rainfall Simulation Hall. The slope of the model could be adjusted manually from 0° to 35°.…”
Section: Experimental Conditions and Equipmentmentioning
confidence: 99%
“…is critical for properly assessing the soil water content and soil water budget dynamics; for example, these processes are critical for baseflow and runoff formation as well as for the transport of excess nutrients from agricultural fields, but are difficult to measure [5][6][7][8]. Soil water content is a key component of the soil water budget and, hence, it contributes to controlling, for example, plant growth [9,10], the availability of water for drainage [11,12] and groundwater recharge [13,14], as well as the transport of contaminants [15,16] and pathogens [17] in the subsurface. Soil water content can in many cases be difficult, time-consuming or expensive to measure [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Lin and Chen 18 studied the effects of straw mulching, polyacrylamide (PAM), and grass strips on the hydraulic properties of red soil, and the results showed that straw mulches significantly improved the moisture content, the water-holding capacity, and the structure of the soil. By exploring the effects of three mulching treatments (bare slope, grassland, and straw mulching) on the physical and chemical properties of the soil, Wang et al 19 concluded that mulches can increase soil moisture content and that organic mulches are the best choices for water retention. Soil moisture and the physical and chemical properties of the soil can be improved by enhancing the water permeability and water-holding capacity of the mulches 20 .…”
Section: Introductionmentioning
confidence: 99%
“…of the soil, Wang et al 19 concluded that mulches can increase soil moisture content and that organic mulches are the best choices for water retention. Soil moisture and the physical and chemical properties of the soil can be improved by enhancing the water permeability and water-holding capacity of the mulches 20 .…”
mentioning
confidence: 99%